Early administration of hydrocortisone vitamin C and thiamine in adult patients with septic shock: a randomized controlled clinical trial - Jaiswal, Shantanu; Singh, Reena; Giri, Richa; Gautam, Shri Krishna; Singh, Mahendra Pal (International Journal of Advances in Medicine, 2025)
Background: Hydrocortisone, vitamin C and thiamine have been suggested as a possible treatment for sepsis and septic shock. However, many trials do not support their use therefore this RCT was conducted to evaluate the efficacy of early administration (within 12 hours of diagnosis) of triple therapy (hydrocortisone, vitamin C and thiamine) in patients of septic shock in north Indian population. The primary objective was to determine the effect of combination on all-cause mortality at day 14. Secondary objectives were change in sofa score at day 3 and day 7, time to shock reversal (in hours) and mean length of hospital stay. Methods: This single centre double blinded RCT was conducted in LLR and Associated hospitals, Kanpur between June, 2023 and June, 2024. The patients were randomly assigned to either Interventional group (n=75) or PLACEBO group (n=75). Interventional group received inj. hydrocort 200 mg once a day, inj. vitamin C 1 gm iv 3 times a day, thiamine 200mg iv 2 times a day for 5 day or until ICU discharge, the patients were then followed up for 14 days. Results: Delta sofa score at day 3 and 7 were not statistically significant (p values- 0.5, 0.241). Significant results were obtained in mean length of hospital stay (11.87 vs 14 days, p value 0.005) and Mean time to shock reversal (176.33 vs 204.40 hours, p value<0.001). Mortality at day 14 was lesser in the interventional group (34.67% vs 45.33%, p value 0.205, statistically insignificant). Conclusions: Thus, in patients with septic shock early treatment (within 12 hours of diagnosis) with injection hydrocortisone, vitamin c and thiamine does not confer mortality benefit but it decreases the length of hospital stay and time to shock reversal.